A Systematic Literature Review of the Effects of Exports, Imports, Exchange Rate, and Inflation on Indonesia’s Economic Growth - Gunawan Aji; Eka Nur Kharisma; Ani Syafa’ah; Elviana Komala Putri; Intan Parwati (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
Economic growth remains a central indicator of national welfare and development, particularlyin emerging economies such as Indonesia. This study systematically reviews empirical findingson how exports, imports, exchange rate fluctuations, and inflation influence Indonesia’seconomic growth. Using a systematic literature review approach, eight peer-reviewed journalarticles published between 2019 and 2023 were analyzed through thematic synthesis drawnfrom Google Scholar and other academic databases. The results reveal that exports consistentlycontribute positively to Indonesia’s gross domestic product (GDP), while the impacts of importsvary depending on domestic industrial capacity and global demand structures. Exchange ratestability is found to enhance trade competitiveness, whereas inflation demonstrates a shortterm but significant effect on growth. The study highlights the interdependence between tradeand monetary variables in shaping macroeconomic performance. Policy implications emphasizethe importance of maintaining external balance, controlling inflationary pressure, and fosteringexport diversification to sustain long-term economic growth in Indonesia.